My grandmother's hands : racialized trauma and the pathway to mending our hearts and bodies - Menakem, Resmaa (Las Vegas, NV : Central Recovery Press, 2017)
"[This book] is a call to action for Americans to recognize that racism is not only about the head, but also about the body. [The author] introduces an alternative view of what we can do to grow beyond our entrenched racialized divide and takes readers through a step-by-step healing process based on the latest neuroscience and somatic healing methods"--Back cover.
Includes bibliographical references.
Library Journal Starred, October 2017
Publishers Weekly, July 2017
Adult
Keywords: African Americans -- Social conditions; Whites -- Race identity -- United States; United States -- Race relations